2015
DOI: 10.1097/01.jaa.0000460929.99918.e6
|View full text |Cite
|
Sign up to set email alerts
|

Community health centers at the crossroads

Abstract: In response to increased demand for primary care services under the Affordable Care Act, the national network of community health centers (CHCs) will play an increasingly prominent role. CHCs have a broad staffing model that includes extensive use of physician assistants (PAs), nurse practitioners (NPs), and certified nurse midwives (CNMs). Between 2007 and 2012, the number of PAs, NPs, and CNMs at CHCs increased by 61%, compared with 31% for physicians. However, several policy and payment issues jeopardize CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The study was set in community health centers (HCs)-an important setting in which to situate this work given their growing role in the U.S. health system, their continued expansion under the ACA (Ku et al 2010;Katz et al 2011; HRSA, The Affordable Care Act and Health Centers n.d.), and their mandate to serve the needs of the medically underserved and vulnerable communities Scope of Practice and Nurse Practitioner Outcomes (Hicks et al 2006;Doty et al 2010). Additionally, while HCs have traditionally and historically relied on a mix of clinicians to deliver care, these providers are increasingly relying on advanced practice clinicians (a categorization that includes NPs, PAs, and nurse midwives), especially NPs (Proser et al 2015). To our knowledge, this is among the first studies to examine the impact of NP restrictions on patient-level outcomes, generally, and the only study to examine this phenomenon in HCs, specifically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study was set in community health centers (HCs)-an important setting in which to situate this work given their growing role in the U.S. health system, their continued expansion under the ACA (Ku et al 2010;Katz et al 2011; HRSA, The Affordable Care Act and Health Centers n.d.), and their mandate to serve the needs of the medically underserved and vulnerable communities Scope of Practice and Nurse Practitioner Outcomes (Hicks et al 2006;Doty et al 2010). Additionally, while HCs have traditionally and historically relied on a mix of clinicians to deliver care, these providers are increasingly relying on advanced practice clinicians (a categorization that includes NPs, PAs, and nurse midwives), especially NPs (Proser et al 2015). To our knowledge, this is among the first studies to examine the impact of NP restrictions on patient-level outcomes, generally, and the only study to examine this phenomenon in HCs, specifically.…”
mentioning
confidence: 99%
“…Additionally, while HCs have traditionally and historically relied on a mix of clinicians to deliver care, these providers are increasingly relying on advanced practice clinicians (a categorization that includes NPs, PAs, and nurse midwives), especially NPs (Proser et al. ). To our knowledge, this is among the first studies to examine the impact of NP restrictions on patient‐level outcomes, generally, and the only study to examine this phenomenon in HCs, specifically.…”
mentioning
confidence: 99%
“…Primary care, rural, and safety-net settings have long suffered the most severe workforce issues of distribution and supply (Beck et al, 2021), and our review shows scant publications in these areas, especially for TTP programs that include PAs. The gap in the literature could potentially be due to a lack of publication of TTP program efforts or the lack of resources to support programs in these settings (Barnes et al, 2018;Owens, 2019;Proser et al, 2015;Zolotor et al, 2022). For example, fellowships and residencies may be more difficult to establish in smaller, community, or safety-net settings than in AHCs.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, onboarding programs might be a better fit for community and safety-net settings that lack academic infrastructure. Because NPs and PAs currently comprise more than half of the providers in these settings (Owens, 2019; Proser et al, 2015; Zolotor et al, 2022), evidence to support new graduates and ensure successful TTP is needed. Our scoping review has identified gaps in the literature that should point researchers and funders to support additional research on TTP support, especially onboarding programs, in primary care, outpatient, rural, and safety-net settings.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent discrepancy between widespread use of holistic review and little if any overall progress toward increasing proportions of URM students also exists in the physician assistant (PA) profession. Created in the late 1960s mainly to address physician shortages in rural communities, PAs, like nurse practitioners, have been increasingly relied on to care for medically underserved patients, who are disproportionately racial and ethnic minorities (Physician Assistant History Society, 2017 ; Proser et al, 2015 ; Shin et al, 2013 ). Therefore, a diverse PA workforce may be particularly important.…”
Section: Introductionmentioning
confidence: 99%